2012
DOI: 10.1590/s1517-83822012000100047
|View full text |Cite
|
Sign up to set email alerts
|

Use of FTA elute card impregnated with cervicovaginal sample directly into the amplification reaction increases the detection of human papillomavirus DNA

Abstract: This study aimed to evaluate the use of the FTA elute cardTM impregnated with cervicovaginal sample directly in the PCR amplification for detection of HPV-DNA. The results were compared to a reference technique. This method was more efficient than the protocol indicated by the manufacturer, identifying 91.7% against 54.2% of the positive samples

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For this reason, high sensitivity primers should be chosen to perform PCRs with FP. Santos (2012) shows that the direct use of the FTA TM elute card in the mix was more effective in identifying HPV-DNA (92% of positive samples) than DNA extracted from the card by elution (54%) 11 . Studies involving Leishmania that used FP for the collection of lesion scrapings, biopsy, or lesion imprint had greater sensitivity (92% to 100%) compared to DS or PCR with DNA obtained from lesion aspirate or biopsy.…”
Section: P C R W a S P E R F O R M E D U S I N G T H E P R I M E R S mentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, high sensitivity primers should be chosen to perform PCRs with FP. Santos (2012) shows that the direct use of the FTA TM elute card in the mix was more effective in identifying HPV-DNA (92% of positive samples) than DNA extracted from the card by elution (54%) 11 . Studies involving Leishmania that used FP for the collection of lesion scrapings, biopsy, or lesion imprint had greater sensitivity (92% to 100%) compared to DS or PCR with DNA obtained from lesion aspirate or biopsy.…”
Section: P C R W a S P E R F O R M E D U S I N G T H E P R I M E R S mentioning
confidence: 99%
“…FP does not appear to interfere with DNA amplification. The increase in temperature of the PCR mix was probably enough for the DNA to escape the FP, thus allowing an efficient reaction 11 .…”
mentioning
confidence: 99%
“…Due to the logistical difficulties such as spillage, flammability, and weight, adding to the risks and costs of liquid transport media, solid carriers consisting of chemically treated or untreated filter paper have been investigated for hrHPV testing. These filter paper cards are easy and safe to store and transport [1][2][3][4][5][6][7][8][9][10][11][12][13]. Recently we (Maurer, et.al.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the card specifically, there has been a series of pilot studies demonstrating that the card, like any self-collection medium, has very good agreement with the clinician-collected sample [310]. In a recently published study, we demonstrated that there was good 90% total agreement, 68% positive agreement and κ-value of 0.75 between a standard specimen medium and paper/card-based medium for HR-HPV detection [11].…”
Section: How Do Self-collection Methods Compare With Traditional Scrementioning
confidence: 99%